Socio-demographic patterns of disability among older adult populations of low-income and middle-income countries: results from World Health Survey - Hosseinpoor, Ahmad Reza (Int J Public Health, 2015)
OBJECTIVE: Our objective was to quantify disability prevalence among older adults of low- and middle-income countries, and measure socio-demographic distribution of disability. METHODS: World Health Survey data included 53,447 adults aged 50 or older from 43 low- and middle-income countries. Disability was a binary classification, based on a composite score derived from self-reported functional difficulties. Socio-demographic variables included sex, age, marital status, area of residence, education level, and household economic status. A multivariate Poisson regression model with robust variance was used to assess associations between disability and socio-demographic variables. RESULTS: Overall, 33.3 % (95 % CI 32.2–34.4 %) of older adults reported disability. Disability was 1.5 times more common in females, and was positively associated with increasing age. Divorced/separated/widowed respondents reported higher disability rates in all but one study country, and education and wealth levels were inversely associated with disability rates. Urban residence tended to be advantageous over rural. Country-level datasets showed disparate patterns. CONCLUSIONS: Effective approaches aimed at disability prevention and improved disability management are warranted, including the inclusion of equity considerations in monitoring and evaluation activities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00038-015-0742-3) contains supplementary material, which is available to authorized users.